2012
DOI: 10.1179/1743281212y.0000000012
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of steelmaking slag by microwave treatment

Abstract: In order to optimise the recovery process of Fe and P from industrial steelmaking slag by microwave irradiation, the recovery ratios of Fe and P from slag-graphite mixtures were investigated. In the reduction of industrial slag by graphite at a fixed microwave processing time of 900 s using a microwave oven, the recovery ratio of Fe increased with increasing carbon equivalent (C eq. : the mole ratio of carbon/oxygen to reduce Fe 2 O 3 and FeO, yielding CO gas) and reached 0?87 when C eq. 51?56. The recovery ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Precipitated phases can be categorized into bottom dross, surface slag and suspended dross. Studies have shown that the bottom dross is δ phase and ζ phase [3,4]. Surface slag mainly consists of oxide types (Zn and/or Al) and Fe 2 Al 5 Zn x [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Precipitated phases can be categorized into bottom dross, surface slag and suspended dross. Studies have shown that the bottom dross is δ phase and ζ phase [3,4]. Surface slag mainly consists of oxide types (Zn and/or Al) and Fe 2 Al 5 Zn x [1,5].…”
Section: Introductionmentioning
confidence: 99%